Laparoscopic Excision of Large Intra-Abdominal Cysts in Children: Needle Hitch Technique - Brice Antao; Jeffrey Tan; Feargal Quinn (Case Reports in Medicine)
Laparoscopic surgery has both diagnostic and therapeutic advantages in the management of intra-abdominal cysts in children. Large cysts in small children pose technical challenges during laparoscopic surgery, requiring multiple incisions and advanced laparoscopic skills. This paper describes a novel laparoscopic technique using minimal manipulation for both aspiration and excision of the cyst. This simple, safe, and effective approach was used to achieve traction and facilitate excision of a large intra-abdominal cyst in a neonate and a young child.